Methicillin-resistant Staphylococcus aureus (MRSA) in men having sex with men (MSM): a systematic review - de Jong, G. M.; van der Boor, S.C.; van Bokhoven, C.; Bos, H.; Hoornenborg, E.; Joosten, R.E.; Notermans, D.W.; de Stoppelaar, S.F. (BMC infectious diseases, 2025)
Background Outbreaks of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) have been documented at multiple sites worldwide. Several studies have reported an elevated infection rate of CA-MRSA infections in men having sex with men (MSM), suggesting CA-MRSA can behave as a sexually transmitted infection (STI). To assess the potential public health impact of CA-MRSA transmission amongst MSM, a systematic review of the literature was conducted to identify risk factors and prevalence of CA-MRSA colonization and infection in MSM. Methods The electronic database Embase.com (containing Embase and Medline) was systematically searched to identify studies investigating CA-MRSA colonization and infection from inception up to 19 January 2024. Two independent reviewers selected potentially relevant articles for full-text screening. Only English-language articles meeting the inclusion criteria were considered. In case of reviewer disagreement, a third independent reviewer was consulted. Information regarding prevalence, strains, and risk factors for CA-MRSA colonization and infection were extracted by one reviewer and checked by a second reviewer. Results 54 studies were screened; 18 were included for analysis. Notably, 3 distinct CA-MRSA clusters were observed in MSM in the USA and Japan. Screening in other MSM cohorts did not reveal an elevated prevalence of CA-MRSA colonization or infection. Identifying as MSM by itself is not a risk factor for MRSA colonization and infection, but specific behavior factors such as intravenous drugs use and high-risk sexual behavior do increase this risk. Discussion Recognizing the potential presence of CA-MRSA in MSM experiencing (skin) infections is crucial for informed clinical decisions. In cases where a cluster of CA-MRSA infections occurs within a sexual network, eradication strategies and non-pharmaceutical interventions should be carefully considered to prevent further spreading. Given the limited available data on this topic and incomplete data on the prevalence on a global scale, further investigations should prioritize studying the impact of CA-MRSA transmission within sexual networks.